Organic nanoparticles as fragmentable support for Ziegler–Natta catalysts. Issue 1 (29th October 2014) - Nietzel, Sven; Joe, Daejune; Krumpfer, Joseph W.; Schellenberger, Frank; Alsaygh, Abdulhamid A.; Fink, Gerhard; Klapper, Markus; Müllen, Klaus
ABSTRACT A fragmentable support material for Ziegler–Natta catalysts is presented based on micrometer‐sized aggregates of polystyrene nanoparticles. Hydroxyl anchoring groups are introduced by copolymerization of hydroxymethylstyrene in emulsion process to immobilize the catalysts. The catalytic activity in ethylene slurry polymerizations is found to be directly correlated to the hydroxyl group content of the supports. Furthermore, the fragmentation behavior of dye‐labeled support aggregates into the initial nanoparticles is demonstrated using laser scanning confocal fluorescence microscopy as a nondestructive method. These supported catalysts fulfill two important design criteria, high fragmentability and high catalyst loading, and produce high‐density polyethylene with medium molecular weight distributions (MWDs = 3–4). These values lie between those obtained using single‐site metallocene‐based (narrow MWD < 3) or inorganic supported multi‐site Ziegler–Natta‐based (broad MWD = 4–12) polymerizations without the need of blending. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 15–22